Audyt językowy w nauczaniu osób dorosłych - Smuk, Maciej (Neofilolog, 2019)
Among the various means used for assessing the general language competences of adult learners, the audit is one of the most popular tools. Apart from its main purpose, which is the diagnosis of current language proficiency, during the audit the learner’s various needs might be as well analyzed. Additionally, we may use this tool to recognize the non-language competences such as: cognitive styles, dominant type of intelligence or learner’s beliefs, attitudes and habits. Thus, the interdisciplinary character of the audit allows, in an exquisite way, to optimize the content of the foreign language course for adults.